2020
DOI: 10.1021/acs.biomac.0c00900
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Cultivation of Artificial Liver Extracellular Matrix in Fibrous Polymer Sponges Biomimicking Scaffolds for Tissue Engineering

Abstract: A major challenge in tissue engineering and artificial scaffolding is to combine easily tunable scaffolds biomimicking the extracellular matrix of native organs with delivery-controlled cell culturing to create fully cellularized, large artificial 3D scaffolds. Aiming at bioartificial liver construction, we present our research using galactose-functionalized, ultraporous polylactide 3D nanofiber sponges fabricated out of electrospun fibers. Sponge biomodification by blend galactosylation and in-solution coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The high porosity of the scaffolds and the resulting rapid flow of medium through the specimens makes it difficult for cell retention and subsequent attachment, which may have led to the observed effect. Functionalization of the PCL nanofibers [80] or the use of a dedicated perfusion bioreactor [43] could overcome this problem. For example, Cause et al showed that aminolyse treatment of PCL nanofibers improved cell adhesion compared to nontreated samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high porosity of the scaffolds and the resulting rapid flow of medium through the specimens makes it difficult for cell retention and subsequent attachment, which may have led to the observed effect. Functionalization of the PCL nanofibers [80] or the use of a dedicated perfusion bioreactor [43] could overcome this problem. For example, Cause et al showed that aminolyse treatment of PCL nanofibers improved cell adhesion compared to nontreated samples.…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution is the production of highly porous three-dimensional (3D) nanofiber sponges or aerogels from short nanofibrous building blocks using a self-assembly process in combination with subsequent freeze drying and cross-linking steps [33][34][35][36][37][38][39][40] or the combination of electrospinning and 3D printing [41]. Recently, several approaches of using preformed nanofibers to assemble 3D nanofiber scaffolds for tissue engineering, in particular for bone, have been reported [42][43][44][45][46][47][48][49][50][51]. This is in contrast to alternative approaches for porous 3D scaffolds, e.g., using sol-gel processes [52].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Following this concept electrospun sponges made of biodegradable polymers, including poly(L-lactide) (PLLA), were reported in recent literature as they are of interest for tissue engineering. [35][36][37][38][39][40][41] For example, Chen et al produced PLLA/gelatin fiber-based sponge with cytocompatibility, which is suitable for cartilage tissue engineering. The hydrophilicity of these sponges was tuned by the addition of gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, electrospun nanofibers are usually assembled into fibrous structures with various shapes, ranging from fibrous yarns [9] and fibrous membranes [10] to fibrous sponges. [11] Yet, due to the intrinsic chaotic structure of electrospun fibers, the mechanical performance of these assemblies is rather weak. Various approaches, including collecting fibers by a high-speed collector, [12] controlling the fiber deposition by adjusting the electrical field, [13] or mechanically aligning the fibers by stretching, [14] have been used to improve the alignment of fiber.…”
Section: Introductionmentioning
confidence: 99%